2003
DOI: 10.1161/01.res.0000099883.68414.61
|View full text |Cite
|
Sign up to set email alerts
|

Two-Pore Domain K Channel, TASK-1, in Pulmonary Artery Smooth Muscle Cells

Abstract: Abstract-Pulmonary vascular tone is strongly influenced by the resting membrane potential of smooth muscle cells, depolarization promoting Ca 2ϩ influx, and contraction. The resting potential is determined largely by the activity of K ϩ -selective ion channels, the molecular nature of which has been debated for some time. In this study, we provide strong evidence that the two-pore domain K ϩ channel, TASK-1, mediates a noninactivating, background K ϩ current (I KN ), which sets the resting membrane potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
171
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(178 citation statements)
references
References 40 publications
5
171
1
Order By: Relevance
“…KCNK3 currents contribute to the resting potential of native PASMCs, and the downregulation or inhibition of KCNK3 causes PASMC depolarization, excessive proliferation, and pulmonary arterial constriction 5, 7, 8, 9. Cultured PASMCs have been used previously to study overexpressed potassium channel activity, regulation, and pharmacology in the context of PAH 19, 20.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KCNK3 currents contribute to the resting potential of native PASMCs, and the downregulation or inhibition of KCNK3 causes PASMC depolarization, excessive proliferation, and pulmonary arterial constriction 5, 7, 8, 9. Cultured PASMCs have been used previously to study overexpressed potassium channel activity, regulation, and pharmacology in the context of PAH 19, 20.…”
Section: Resultsmentioning
confidence: 99%
“…The voltage‐insensitivity of KCNK3 renders the channel open across all voltages, leading to potassium efflux from cells expressing the channel, which contributes to the negative resting potential. KCNK3 is widely expressed in the human body, including in the central nervous system, heart, and pulmonary artery smooth muscle cells (PASMCs) 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…Because the K 2P channels are typically open at negative membrane potential, they have been strongly implicated in establishing the background K + conductance known to stabilise the negative resting membrane potential and counterbalance depolarisation [78]. KCNK3 (also called TASK1) encodes a pH-sensitive K 2P channel, which has been shown to be expressed by PASMCs and to contribute significantly to the resting membrane potential [79]. Indeed, TASK1 knockdown in human PASMCs caused a depolarisation of the resting membrane potential [80].…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Cmentioning
confidence: 99%
“…Furthermore, Kindler et al (2000) showed that the same antibody was specific for TASK-1 when used to probe sections taken from various regions of the rat central nervous system. Recently, this antibody was also used to probe rabbit pulmonary artery myocytes (Gurney et al, 2003). The anti-TASK-2 antibody used also binds specifically to TASK-2 in rat tissue (Gabriel et al, 2002) as well as in cultured Ehrlich cells (Niemeyer et al, 2001).…”
Section: Mj Gardener Et Almentioning
confidence: 99%
“…Although none of the channel modulators used should be regarded as selective, the results collectively suggest that TASK-1 channels in particular are of functional significance. Of note is the evidence that the potassium current designated I KN (Gurney et al, 2002) is carried by TASK-1 in pulmonary myocytes derived from rabbit pulmonary arteries (Gurney et al, 2003). This current, which is reduced in chronic pulmonary hypoxia and is important in setting resting membrane potential in pulmonary vessels (Evans et al, 1998), implicates TASK-1 in hypoxic disease states.…”
Section: P-domain Kmentioning
confidence: 99%